A Study to Evaluate Prescribing Indicators of Prescription Pattern Practiced by Interns in an Urban Health Center - S, Ajit; P, Sanjay; R.R, Shinde (Indian Journal of Pharmacy Practice)
Background: It is essential that the prescribing and administration of drugs should be evaluated from time to time, to quantify the error in such procedures, and look for possible solutions for an effective utilization of the enormous resources spent on drugs. Objectives: To evaluate prescribing indicators of prescriptions using WHO recommended tools for core drug use and the quality of prescriptions in terms of expected norms of format of prescriptions. Methods: The study was carried out in urban health center attached to teaching college with Informal experimental design. Sample size was 230 prescriptions of interns from each group. The prescriptions were selected using systematic random sampling technique and evaluated. Knowledge of patients regarding prescriptions was assessed. Results: The average number of drugs prescribed per prescription was found to be 3.2 ± 1.106. Percentage of drugs prescribed by generic name was increased in study group (66.1%) as compared to from in control group (43%). Percentage of drugs prescribed from essential drug list was increased from 19.6% in control group as compared to 34.3% in study group. There was significant improvement in writing superscription, inscription, and transcription in the study group as compared to control group. Patient's knowledge regarding prescription also improved in few aspects in the study group as compared to control group. Conclusion: Structured training on pharmacotherapy based on workshop pattern with focus on problem solving exercises can be helpful to improve prescribing skills of interns and may be introduced in regular internship orientation programme.
Keywords: Prescription; Prescribing indicators; intern